Intervenciones de enfermería y su relación con la prevención de las enfermedades crónicas no transmisibles de los adultos mayores del Hospital Básico Dr. José Cevallos Ruiz, octubre 2024-mayo 2025. - León Herrera, Martha Yamileth (2024)
The objective of the study was to analyze the relationship between nursing interventions and the prevention of chronic noncommunicable diseases (NCDs) in older adults cared for at the Dr. José Cevallos Ruiz Basic Hospital between October 2024 and May 2025. Regarding the methodology, a research with a quantitative approach and descriptive level was developed, using a non-experimental design to observe and analyze nursing actions without manipulating variables. The population demonstrated for this study was made up of 34 nursing professionals who work at the Dr. José Cevallos Ruiz Basic Hospital, during the period October 2024-May 2025. Regarding the technique used, the survey was used, which consists of analyzing nursing professionals in order to collect relevant data on the interventions applied to older adult patients. In conclusion, the analysis of the relationship between interventions for the prevention of chronic non-communicable diseases determines the comprehensive and preventive care to optimize the quality of life and reduce complications in older adults. Health adaptation, personalized follow-up and periodic control are important keys for this type of process. It is recommended to strengthen nursing interventions based on prevention based on a health education program and periodic control in older adult patients. This will help reduce complications and improve the lifestyle of patients.